2009
DOI: 10.1101/lm.1310209
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid beta mediates memory formation

Abstract: The amyloid precursor protein (APP) undergoes sequential cleavages to generate various polypeptides, including the amyloid β (1–42) peptide (Aβ[1–42]), which is believed to play a major role in amyloid plaque formation in Alzheimer's disease (AD). Here we provide evidence that, in contrast with its pathological role when accumulated, endogenous Aβ in normal hippocampi mediates learning and memory formation. Furthermore, hippocampal injection of picomolar concentrations of exogenous Aβ(1–42) enhances memory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 55 publications
13
108
0
1
Order By: Relevance
“…Our laboratory and others have previously demonstrated that Aβ can have positive modulatory effects on synaptic plasticity and cognition at non-pathological, low picomolar concentrations [911]. Specifically, we demonstrated that both hippocampal long-term potentiation (LTP) and hippocampal-dependent learning and memory can be enhanced by the acute administration of 200 pM Aβ 42 [9].…”
Section: Introductionmentioning
confidence: 76%
“…Our laboratory and others have previously demonstrated that Aβ can have positive modulatory effects on synaptic plasticity and cognition at non-pathological, low picomolar concentrations [911]. Specifically, we demonstrated that both hippocampal long-term potentiation (LTP) and hippocampal-dependent learning and memory can be enhanced by the acute administration of 200 pM Aβ 42 [9].…”
Section: Introductionmentioning
confidence: 76%
“…This concentration range of A β was also measured in the ISF of mice subjected to a circadian rhythm, with more elevated levels when awake (Kang et al , 2009 ). Moreover, other authors reported that A β levels in the picomolar range enhanced synaptic plasticity and memory (Puzzo et al , 2008 ;Garcia -Osta and Alberini, 2009 ). Thus, these data support the idea that A β secretion could be a physiological event occurring with normal brain activity.…”
Section: App Metabolism and A β Formationmentioning
confidence: 90%
“…Interestingly, there have been prior rodent behavior studies that involve external delivery of Aβ 1-42 directly into the brain. 22,30 Taken together, these limitations need to be considered when designing in vivo mouse studies employing this model.…”
Section: Discussionmentioning
confidence: 99%